Um panorama de pesquisas sobre o uso da modelagem matemática no ensino médio: 2010 a 2014 - Santos, Douglas Borreio Maciel dos (2016)
This thesis presents a survey conducted under the Master Academic Program of Postgraduate Studies in Mathematics Education from PUC-SP. It is a bibliographic theoretical research of the type state of the art that targets develop a Panorama Research whose theme is the use of mathematical modeling in high school: in the period 2010 to 2014. The objective of Panorama is to systematize the two main elements of a modeling: the phenomenon to be modeled and the mathematical concept modeler. The data were selected from the search of dissertations and articles in the thesis database of CAPES, the Digital Library of PUC-SP and on the Internet (using the Google search engine). The study included the analysis of twenty-one dissertations and seven articles. It was observed that the 28 most studies analyzed, 18 of them used as the modulator function concept, still showing complex numbers, arithmetic progressions, geometric progressions three rule and proportionality constant spatial geometry and redemption system. And they were presented as a phenomenon to be modeled for example semidesintegração cesium and iodine; the study of the automobile supply due to the movement, optimizing the use of alcohol or petrol in a car race; study the advantages and disadvantages in the use of nuclear power plant to the environment; the apparent movement of the sun and the length of shadows among others